Intraoral Vascular Malformation of Right Cheek: A Case Report (Academia Journal of Medicine, 2026)
This is a case report of an adult untreated vascular malformation of the cheek,involving the masseter muscle, which underwent recent enlargement. Afterconsideration of different treatment options, intraoral excision of the malformation was done including intramuscular dissection. There was no recurrence on short term follow up.